RANCANG BANGUN KELISTRIKAN PADA MESIN BAWANG MERAH DAN BAWANG BOMBAY TENAGA HYBRID - Mirza, Muhammad; Ramdani, Rizki (Jurnal Mahasiswa Terapan; Vol 1 No 1 (2024): Jurnal Mahasiswa Terapan, 2024)
The process of manually slicing shallots often takes a long time and requires a lot of labor so that UMKM who own the business have to spend more budget to fulfill responsibilities to employees. Therefore, an onion and onion slicing machine was developed which is designed to increase efficiency and productivity in processing shallots and onions to create fast work that can produce more production than using manual labor. That way this machine is very useful for UMKM who have a limited budget to start trying this machine is designed using the working principle of a rotating knife driven by an electric motor that gets flow from an electric current and can also use battery power through an inventer as an alternative power source for onion slicing machines that have two power source options: electric motor and battery power through an inverter.